PERKEMBANGAN PENDIDIKAN DAN KELAINAN PADA MURID - Saguni, Fatimah (Hunafa: Jurnal Studia Islamika, 2007)
In psychology, development is a change to a better value. Development can be observedÂ  from the aspects that form it, that is physical and non-physical aspects while growth relates to a mere physical change. Therefore, education development involves both physical and non-physical factors. As far as a pupilâs disorder, the two factors should be given close attention.Kata Kunci: Perkembangan pendidikan, kelainan pada murid